Multiple drug resistant tuberculosis in patients addicted to alcohol – a critical issue of the current tuberculosis control - I. S. Gelbert; S. B. Volf; E. N. Alekso; Yu. A. Sheyfer; V. S. Avlasenko (Туберкулез и болезни лёгких)
The article presents the comparative description of multiple resistant tuberculosis patients (MDR TB) abusing alcohol (group 1 – 169 people), and not abusing alcohol (group 2 – 122 persons); the frequency and specificity of adverse reaction to anti-tuberculosis drugs, immediate and postponed treatment outcomes have been studied. The negative effect of the alcohol abuse on the majority of the studied rates has been found out. Disseminated forms, fibrous cavernous tuberculosis, intoxication syndrome, chronic respiratory, intestinal and liver diseases, as well as incarceration experience are observed more often among alcohol dependent MDR TB patients. It is confidently true that adverse reactions occur more often (84.6% versus 57.6%), including toxic reactions, they are more severe and intractable, especially hepato- and neuro-toxic ones.Efficiency of in-patient treatment is confidently lower in the 1st group – 61.7% versus 82.8%. The cessation of bacillary excretion was lower (69.7% versus 85.6%). The hospital mortality was also higher in the 1st group (8.6% versus 0.9%).The postponed results of 2 – 6 year follow up are worse in the patients abusing alcohol. The successful treatment outcomes with criteria of cured, treatment completed were observed in the 60.4% in the 1st group of patient, while in the 2nd group this rate made 80.8% (p < 0.05), the mortality and disability rates were also higher as well as the number of patients in whom bacillary excretion persisted (38.3% versus 19.2%, p < 0.05).70% of patients demonstrated favorable treatment outcomes.